Eicosanoid Production following One Bout of Exercise in Middle-Aged African American Pre- and Stage 1 Hypertensives - Sheara Williamson; Deepti Varma; Michael Brown; Susan Jansen (Journal of Aging Research)
Endothelial dysfunction and a sedentary lifestyle may be involved in the development of hypertension which is proliferative among middle-aged African Americans (AA). Signaling molecules derived from the oxidation of 20-carbon fatty acid molecules known as eicosanoids influence vascular tone. The relationship between aerobic fitness and eicosanoid formation following exercise in middle-aged African American hypertensives is unknown. Purpose. To determine the relationship between aerobic capacity and eicosanoid formation after a bout of moderate-intensity exercise in middle-aged AA hypertensives. Methods. Ten sedentary hypertensive AA underwent 50 min of aerobic exercise at 65% VO2max. Urine was collected for 24 hr on two occasions, prior to testing and immediately following the bout of exercise. Urinary metabolites of prostacyclin (6-keto PGF1α) and thromboxane (11-dTXB2) were measured during the day and night periods by high-performance liquid chromatography (HPLC). Results. 6-keto PGF1α levels significantly increased (𝑃=.04) following the bout of exercise compared to the control day. There was a significant relationship (𝑟=.49, 𝑃<.05) between 6-keto PGF1α levels and VO2max during the exercise day. Conclusion. Based on this preliminary study, there appears to be a relationship between aerobic capacity and exercise-induced 6-keto PGF1α production in middle-aged hypertensive AAs. AAs with lower VO2max had lower 6-keto PGF1α formation.